Can MRI related patient anxiety be prevented? - TÜNEY, DAVUT (ELSEVIER SCIENCE INC, 2015)
Purpose: To evaluate the effectivity of a combined intervention of information and communication to reduce magnetic resonance imaging (MRI) anxiety using prolactin and cortisol as biochemical markers and State Trait Anxiety Inventory (STAI). Materials and methods: This study is a randomized prospective research. Sample size was 33 patients. Fourteen patients were enrolled as study group, compared to 19 patients as control group. Blood samples were collected by venous sampling, and STAI was filled before and after scan. State anxiety inventory was used twice. Study group received a standard information about MRI scans and were communicated with 2 minute intervals via intercom; control group had no intervention. Blood samples were carried in ice to be centrifuged and stored as soon as they were taken to study prolactin and cortisol. Data were stored and analyzed by SPSS 17.0. P value for significance was accepted as 0.05. Results: Prolactin-pre, prolactin-post, cortisol-pre, cortisol-post, cortisol percent increase, Trait Anxiety Inventory (TAI), SAL (State Anxiety Inventory) pre-scan and post-scan levels were similar between demographic groups. Cortisol-pre levels were similar between study and control, however prolactin-pre levels were significantly higher in control group. Study group had 6% lower cortisol level post-scan, whereas control group had 18% increase. Study and control groups had similar Trait Anxiety and SAI-pre scores. SAI-post scores were lower in study group when compared with control group. Study group also had lower SAI-post scores than SAI-pre, whereas control group had higher. Conclusion: MRI anxiety can be reduced by information and communication. This combined method is shown to be effective and should be used during daily radiology routine. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Magnetic resonance imaging; Anxiety; Prolactin; Cortisol; State trait anxiety inventory; RESONANCE; CLAUSTROPHOBIA; CORTISOL